Pengaruh Tekanan Finansial, Efektivitas Pengendalian Internal, dan Budaya Organisasi Terhadap Kecenderungan Kecurangan (Fraud) dengan Integrasi Teknologi Sebagai Variabel Moderasi pada Lembaga Perkreditan Desa di Kecamatan Dawan: The Influence of Financial Pressure, Effectiveness of Internal Control, and Organizational Culture on the Tendency of Fraud with Technology Integration as a Moderating Variable in Village Credit Institutions in Dawan District - Kadek, Ni Kadek Astiti Pratiwi; Gusti Ayu Ketut Rencana Sari Dewi (Vokasi : Jurnal Riset Akuntansi, 2023)
This research aims to determine the influence of financial pressure, the effectiveness of internal control, and organizational culture on the tendency of fraud with technology integration as a moderating variable in Village Credit Institutions (LPD) in Dawan District. The research uses primary data obtained from questionnaires and is measured on a likert scale. The population in this study consists of all officials in 19 LPDs in Dawan District. The sample was determined using a saturated sampling technique, resulting in a total of 87 respondents. Data were analyzed using descriptive statistical tests, data quality tests, classic assumption tests, multiple linear regression analysis, moderated regression analysis, and t-tests with data presentation assisted by SPSS version 25. The research results indicate that: (1) financial pressure has a significant positive effect on the tendency of fraud, (2) the effectiveness of internal control has a significant negative effect on the tendency of fraud, (3) organizational culture does not influence the tendency of fraud, and (4) technology integration is capable of moderating the influence of financial pressure and the effectiveness of internal control on the tendency of fraud, but it is not able to moderate the influence of organizational culture on the tendency of fraud.